SKILLS IN USING DIGITAL TECHNOLOGIES IN INTERNATIONAL FOOTBALL (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
The integration of digital technologies into international football has revolutionized the way the sport is played, managed, and consumed. From advanced performance tracking and video analytics to artificial intelligence in scouting and fan engagement through virtual platforms, digital transformation is reshaping every facet of the game. Leading football nations and clubs are actively investing in technology to enhance player development, improve team strategies, and create immersive experiences for global audiences. This paper explores the key areas where digital technologies are being utilized in international football, drawing on global case studies and research to highlight their practical applications. By analyzing current trends, innovations, and outcomes, this study offers insights into how digital tools contribute to the modernization of football and what lessons can be learned for countries like Uzbekistan seeking to elevate their football infrastructure and competitiveness through technology.